Crustacean cardioactive peptide and its receptor modulate the ecdysis behavior in the pea aphid, Acyrthosiphon pisum. (February 2022) - Shi, Yan; Liu, Tian-Yuan; Ding, Bi-Yue; Niu, Jinzhi; Jiang, Hong-Bo; Liu, Tong-Xian; Wang, Jin-Jun
Graphical abstract: Highlights: Heterologous expression was performed to confirm CCAP-R functional of A. pisum . APCCAP neurons were located by immunohistochemistry in the central nervous system. With RNAi of CCAP signaling, a molting failure and dead were observed and counted. Abstract: Insects must undergo ecdysis for successful development and growth, in which crustacean cardioactive peptide (CCAP) is a master hormone. However, the function of CCAP signaling in pea aphid, Acyrthosiphon pisum, remains unclear. In this study, we determined the sequence of the CCAP precursor and its receptor in A. pisum . We identified the functional receptor ApCCAPR, and then expressed this receptor in Chinese hamster ovary (CHO) cells, which in consequence exhibited high sensitivity to the ApCCAP mature peptide. The ApCCAP transcript was detected in the central nervous system of A. pisum . Neurons containing CCAP were also identified by immunohistochemical staining against insect CCAP. RNAi silencing of ApCCAP or ApCCAP-R signals caused developmental failure during nymph–adult ecdysis. The dsRNA-treated fourth-instar nymphs could not shed their old cuticle and died. Taking these findings together, we conclude that ApCCAP, via the activation of ApCCAP - R, plays an essential role in regulating the process of nymph–adult ecdysis in A. pisum . Our results deepen our understanding of the regulation of early ecdysis in A. pisum .